Keplerate Polyoxotungstate Nanowheel Functionalized Magnetic Nanoparticles for Sustainable Biodiesel Production by Esterification of Free Fatty Acids with Ethanol in an Ultrasound-Assisted - Haddad, Reza (Current Catalysis, 2016)
Background: Biodiesel is briefly defined as the monoalkyl esters of vegetable oils or animal fats. Biodiesel is the best candidate for diesel fuels in diesel engines as a
Keywords: Polyoxotungstate